Comparison of lots of pea seeds produced in northwest of Paraná - Wenneck, Gustavo Soares; Volpato, Camila de Souza; Saath, Reni; Ghuidotti, Gabriela Cristina; Silva, Richard Eduardo Quintino da (Acta Iguazu, 2021)
The establishment of the crop demands the use of seeds that allow the plants to perform better in adverse conditions. The study aimed to compare lots of pea seeds produced in the northwestern region of Paraná. The experiment was carried out in a completely randomized design with seven seed lots and four replications. The seeds were obtained in field production, with similar management conditions. The determination of the weight of a thousand seeds, water content, electrical conductivity, percentage of germination, fresh and dry mass of the aerial part and root of the seedlings performed. The data were subjected to analysis of variance and the means compared by the Tukey test with 5% significance. The physiological potential not directly related to the seed mass; of the pea lots produced under adverse conditions, lots L3 and L4 showed superior quality. The physiological tests of electrical conductivity and germination differentiated the quality of the seeds. According to the selection criteria, the seeds of four pea lots showed germination higher than 85%, being the seeds of the lot L3 and L4 presented superior quality.